154k views
1 vote
Please help with this i would be so glad and happy.

Please help with this i would be so glad and happy.-example-1

1 Answer

3 votes

Answer:

Explanation:

d) (-2 +4i) -( 3 + 9i) = -2 + 4i - 3 - 9i

= -2 - 3 + 4i - 9i

= -5 - 5i

e)3i(6 - 5i) = 3i *6 - 5i * 3i

= 18i - 15*i² {i² = -1}

= 18i -15*(-1)

= 18i + 15

= 15 + 18i

f) (-3 + 7i)(1 - 2i) = (-3)*1 - 2i * (-3) + 7i *1 - 2i* 7i

= -3 + 6i + 7i - 14i²

= -3 + 6i + 7i - 14*(-1)

= -3 + 6i+ 7i + 14

= 11 + 13i

User Nids Barthwal
by
4.6k points